The Effectiveness of the Composition of Banana Peel Vinegar and NaCl as Fish Preservative - Rifqi Athawirya; Siti Mardiyah; Sudirman Sudirman; Fitrotin Azizah; Aini Ahmad (International Journal of Advanced Health Science and Technology, 2022)
Fish is a food that is in great demand by many people. Fish are also easily damaged. Therefore, some fishermen use formalin as a preservative for their caught fish. However, the use of formalin in food is prohibited and is considered dangerous because it can cause health problems. Hence, the use of natural preservatives is an alternative. The combination of banana peel vinegar and NaCl salt used banana peel vinegar can inhibit the growth of microbes in the fish body. Furthermore, if it is combined with the addition of NaCl, it can reduce the water content in the fish body so that microbes cannot grow and reproduce. The purpose of this study was to obtain an effective concentration of preservatives from the combination of banana peel vinegar and NaCl. This type of research is experimental with 4 treatments 9:1, 7:1, 4:1, and 3:1. Each treatment was repeated 6 times. 24 samples of fish that have been treated are left for 12 hours at room temperature which represents the time fishermen catch fish until they come to shore. The results of this study showed that the durability of fresh fish in 4:1 treatment got a value of 6.95, categorized as fresh fish. It means that the combination of banana peel vinegar and NaCl salt at a concentration of 4:1 is effectively used as a fish preservative. The results of the oneway ANOVA test showed that there was an effect of the combination of banana peel vinegar and NaCl salt on the freshness of the fish.